2010
DOI: 10.1002/adma.200901846
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Dimensional Control of High‐Capacity Li‐Ion‐Battery Anodes: From 0D Hollow to 3D Porous Germanium Nanoparticle Assemblies

Abstract: Simple physical blending of SiO2 and ethyl‐capped Ge gels leads to flexible dimensional control of Ge nanoparticles, and an increasing weight fraction of the latter leads to ordered 3D porous nanoparticle assemblies (see figure). The long‐range ordering of the 3D porous Ge nanoparticles and their very thin pore wall thicknesses (<20 nm) induce excellent cycling performance, showing only a 2% capacity decrease after 100 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
276
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(287 citation statements)
references
References 38 publications
8
276
2
1
Order By: Relevance
“…The 3D porous nanoparticles prepared by Park et al (Fig. 7) [66], displayed excellent capacity retention and structural stability over 100 cycles at C rate, compared to their non-porous, 0D counterparts. The zero-dimensional (0D) Ge nanoparticles did not sustain their structure on alloying, resulting in marked loss of capacity over successive cycles.…”
Section: Germaniummentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D porous nanoparticles prepared by Park et al (Fig. 7) [66], displayed excellent capacity retention and structural stability over 100 cycles at C rate, compared to their non-porous, 0D counterparts. The zero-dimensional (0D) Ge nanoparticles did not sustain their structure on alloying, resulting in marked loss of capacity over successive cycles.…”
Section: Germaniummentioning
confidence: 99%
“…Other candidates of note include porous Ge nanostructures [66][67][68] and GeOx hierarchical structures [69], which have displayed enhanced performance owing to their porous structuring. The 3D porous nanoparticles prepared by Park et al (Fig.…”
Section: Germaniummentioning
confidence: 99%
“…In previous studies, germanium-based materials with unique nanostructures, such as nanowires, [12,13] nanotubes, [3] and/or carbonaceous support materials, presented various attractive features as advanced electrode materials for lithium ion batteries. Furthermore, strategies directed towards the synthesis of porous [10] or mesoporous [14] structures have been applied to fully realize the good electrochemical properties of germanium due to the facilitated lithium diffusion and increased active area between the electrode materials and electrolyte. It has been widely accepted that carbon coating is the simplest and most effective approach to improve the electrochemical performance of germanium, which can be ascribed to its effects towards suppressing the volume changes and particle agglomeration, and enhancing electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely accepted that carbon coating is the simplest and most effective approach to improve the electrochemical performance of germanium, which can be ascribed to its effects towards suppressing the volume changes and particle agglomeration, and enhancing electrical conductivity. [9][10][11]13] A series of germanium-based materials have been synthesized by a facile method of carbon coating and reduction of germanium oxide precursor that was developed in our previous research. [2,15,16] We found that small particle size, and continuous and robust carbon coatings have significant effects that promote excellent electrochemical properties in germanium anode materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, much research has been focused on high capacity materials such as silicon (4200 mAh/g), [1][2][3][4][5][6] germanium (1623 mAh/g), [7][8][9][10][11][12][13] and tin (993 mAh/g) [14][15][16][17][18][19] to replace the graphite anode. The oxides of these metals (SiO, [20][21][22][23] Germanium dioxide nanoparticles have been previously studied as anode material for LIBs and were reported to react with up to 9 Li + during the first discharge cycle.…”
mentioning
confidence: 99%